1990
DOI: 10.1017/s0950268800059422
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sanitation, food and water contamination and diarrhoea in rural Bangladesh

Abstract: SUMMARYThis study examined the role of food and water contamination in a health impact evaluation of a water and sanitation intervention project. Although lower diarrhoea rates were found in the improved area no consistent difference in food and water contamination was observed between areas. Furthermore, no relationship was found between contamination and diarrhoea in either area, even after controlling for the nutritional status of children. These results imply that other vehicles of transmission might be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…In this study, we found no consistent association between water quality indicators and diarrhea among children 5 years of age (Table 5). A lack of association between water quality indicators and child diarrhea is consistent with findings from studies in Bangladesh, 15 Pakistan, 17 and Ecuador 19 but stands in contrast to findings from studies in the Philippines 16 and Cambodia. 18 These variable results between study sites are not unexpected given regional differences in the non-fecal contributions to microbial indicator levels and in the relative importance of drinking water as a disease transmission pathway.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, we found no consistent association between water quality indicators and diarrhea among children 5 years of age (Table 5). A lack of association between water quality indicators and child diarrhea is consistent with findings from studies in Bangladesh, 15 Pakistan, 17 and Ecuador 19 but stands in contrast to findings from studies in the Philippines 16 and Cambodia. 18 These variable results between study sites are not unexpected given regional differences in the non-fecal contributions to microbial indicator levels and in the relative importance of drinking water as a disease transmission pathway.…”
Section: Discussionsupporting
confidence: 76%
“…[10][11][12] These observations reflect the variable relationships observed between water quality indicators and actual fecal pathogens, 13,14 which may also contribute to the weak and inconsistent associations between water quality indicators and diarrheal disease. 2,13,[15][16][17][18][19] Most of the validated methods for quantifying total coliforms, thermotolerant coliforms, and E. coli in drinking water are costly and require both dedicated facilities and specialized training. To promote on-site microbial water testing in resource-poor settings, Manja and others 20 developed a simple presence/absence test for hydrogen sulfide (H 2 S)-producing bacteria, based on the observation that coliform bacteria in drinking water were consistently associated with H 2 S production.…”
Section: Introductionmentioning
confidence: 99%
“…Site I downstream of this river was found to be more contaminated than site II upstream probably due to human and animal faecal contamination. The contamination of natural water sources by faecally derived organisms has been reported elsewhere [6,19,20]. Pipeborne treated water from comparatively older Mambogo distribution system had higher microbial counts than water from a dam on the relatively new Mafiga distribution system.…”
Section: Resultsmentioning
confidence: 80%
“…Recent evaluations of intervention studies have concluded that it is less cost effective to combat diarrhoeal diseases through water purification than through increases in water quantity or improving exereta disposal [317][318][319]. The results of this study emphasize the need to distinguish between, rather than lump together, the various diarrhoeal pathogens when making conclusions.…”
Section: Relevance Of the Correlationmentioning
confidence: 82%